DIAGNOSTIC AND CLINICAL EFFECTIVENESS OF TELEMEDICINE TECHNOLOGIES IN RADIATION DIAGNOSIS - T. S. Smal; V. D. Zavadovskaya; I. A. Deyev (Бюллетень сибирской медицины, 2016)
The paper reviewed the definition of terminology and the history of the development of telemedicine. The main directions of development of telemedicine technologies in Russia and abroad. Provides information about the different areas of information and communication technologies in health care. Presented as a variety of telemedicine services for medical purposes. The main problem hindering the development of Telemedicine and Medical Radiology in particular.